2013
DOI: 10.1080/09593330.2013.827746
|View full text |Cite
|
Sign up to set email alerts
|

Butanol fermentation

Abstract: This review provides an overview on bacterial butanol production and recent developments concerning strain improvement, newly built butanol production plants, and the importance of alternative substrates, especially lignocellulosic hydrolysates. The butanol fermentation using solventogenic clostridial strains, particularly Clostridium acetobutylicum, is a very old industrial process (acetone-butanol-ethanol-ABE fermentation). The genome of this organism has been sequenced and analysed, leading to important imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 143 publications
0
42
0
Order By: Relevance
“…As examples, Clostridium acetobutylicum and Clostridium butyricum are well known to produce acetone-butanol-ethanol (ABE) products during industrial fermentation (3). Clostridium beijerinckii can be used to produce butanol (4), while Clostridium cellulolyticum can use cellulose as a carbon source and generate lactate, acetate, and ethanol as valuable end products (5).…”
mentioning
confidence: 99%
“…As examples, Clostridium acetobutylicum and Clostridium butyricum are well known to produce acetone-butanol-ethanol (ABE) products during industrial fermentation (3). Clostridium beijerinckii can be used to produce butanol (4), while Clostridium cellulolyticum can use cellulose as a carbon source and generate lactate, acetate, and ethanol as valuable end products (5).…”
mentioning
confidence: 99%
“…These results revealed that extracellular electron transfer molecules influenced the fermentative metabolism of butanol-producing clostridia on different scales by stimulating or interfering with hydrogen formation. On the other hand, C. acetobutylicum and C. beijerinckii have similar butanol synthetic pathways and regulatory mechanisms (2,3,17). However, C. acetobutylicum grew poorly and produced less solvent than C. beijerinckii using DTH as the carbon source (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…These genes encoded acetoacetate decarboxylase (adc, Cbei_3835), alcohol dehydrogenase (ald, Cbei_3832), thiolase (thl, Cbei_3630), butyryl-CoA dehydrogenase (bcd, Cbei_0325), nicotinic acid mononucleotide adenylyltransferase (nadD, Cbei_0513), thioredoxin reductase (trxB, Cbei_2681), and Ni/Fe hydrogenase (hyd, Cbei_3013). The adc, ald, thl, and bcd genes are located in the central butanol and acetone synthetic pathway (2,32). The nadD gene is located in the NAD(H) biosynthesis pathway (33), and the hyd gene is involved in hydrogen formation in C. beijerinckii (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is now increasing interest in the use of biobutanol as a transport fuel given its many advantages [1]. In fact, a number of companies (such as BP-DuPont and Abengoa) are now investigating novel alternatives to traditional production process, which would enable A C C E P T E D M A N U S C R I P T biobutanol to be produced on an industrial scale [2].…”
Section: Introductionmentioning
confidence: 99%